Serum folate, vitamin B12 levels and clinicohematological profile in 200 anaemic children aged 1-5 years - Arora, Sunita; Sheemar, Pushpjeet Singh; Khurana, Mandeep Singh; Kaur, Jaskiran; Kumar, Ashwani (International Journal of Contemporary Pediatrics, 2018)
Background: This study was conducted in 200 anaemic children aged 1-5 years to check their serum folate, vitamin B12 levels and their correlation with sociodemographic parameters and clinicohaematological profile. Methods: Present study was a hospital based observational cross-sectional study carried out in paediatric OPD and IPD of tertiary care institute in Amritsar. Study subjects included 200 anaemic children aged 1-5 years attending paediatric OPD or admitted in IPD of paediatrics department of SGRDIMSAR, Amritsar. Serum folate, vitamin B12 levels were measured in 200 enrolled anaemic children and their correlation with sociodemographic parameters and clinicohaematological profile was studied. Results: Isolated vitamin B12 deficiency was present in 22 (11%), folate deficiency in 28 (14%) and combined deficiency was present in 10 (5%) cases. Isolated vitamin B12 deficiency was more prevalent in 1-2-year age group 10 (45.5%) cases, isolated folate deficiency in 2-3 years age group 12 (42.9%) cases whereas combined deficiency was more prevalent in 4-5 years age group 6 cases (60%). Statistically significant correlation was observed between severity of anaemia and poor socio-economic status, nutritional status, rural background. There was statistically significant association between vitamin B12 deficiency and poor socioeconomic status. Folate and combined deficiency had a positive correlation with age group. Combined vitamin B12 and folate deficiency had a statistically significant correlation with severity of anaemia. Conclusions: Apart from iron deficiency anaemia, vitamin B12 and folate deficiency contributes significantly in total prevalence of anaemia. Vitamin B12 and folate supplementation is equally important in prevention as well as treatment of nutritional deficiency anaemias in paediatric population.